Tadhad: Fenomena Sosio-Kultural dalam Bahasa Arab - Apriwanto Apriwanto (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
This paper discusses the phenomenon of tadhad in Arabic. Tadhad is a lingual phenomenon that is unique in Arabic and has not been found in other languages. It is a word that has two conflicting meanings. In the dialectic of thought, scholars differed on the existence of tadhad in Arabic. Some of them agree and others deny it. Both parties expressed their arguments with the various arguments they used. Among the factors of the emergence of Al-Tadhad are as follows: (1) The origin of a sentence is used in the opposite general meaning; (2) Tadhad arises because of the social factors found in the Arabs. Among these factors are tafaa'ul (wishing good) and tahakkum (mocking); (3) Harmony between two words in one shighat sharfiyah (a form of changing words); (4) Differences in the ranks of the Arab tribes in using a sentence (5) Language development. Examples of the application of tadhad in Arabic can be found in various verses in the Qur'an.